Cell aggregation promotes pyoverdine-dependent iron uptake and virulence in Pseudomonas aeruginosa - Visaggio, Daniela; Pasqua, Martina; Bonchi, Carlo; Kaever, Volkhard; Visca, Paolo; Imperi, Francesco (Frontiers in Microbiology, 2015)
In Pseudomonas aeruginosa the Gac signaling system and the second messenger cyclic diguanylate (c-di-GMP) participate in the control of the switch between planktonic and biofilm lifestyles, by regulating the production of the two exopolysaccharides Pel and Psl. The Gac and c-di-GMP regulatory networks also coordinately promote the production of the pyoverdine siderophore, and the extracellular polysaccharides Pel and Psl have recently been found to mediate c-di-GMP-dependent regulation of pyoverdine genes. Here we demonstrate that Pel and Psl are also essential for Gac--mediated activation of pyoverdine production. A pel psl double mutant produces very low levels of pyoverdine and shows a marked reduction in the expression of the pyoverdine-dependent virulence factors exotoxin A and PrpL protease. While the exopolysaccharide-proficient parent strain forms multicellular planktonic aggregates in liquid cultures, the Pel and Psl-deficient mutant mainly grows as dispersed cells. Notably, artificially-induced cell aggregation is able to restore pyoverdine-dependent gene expression in the pel psl mutant, in a way that appears to be independent of iron diffusion or siderophore signaling, as well as of recently-described contact-dependent mechanosensitive systems. This study demonstrates that cell aggregation represents an important cue triggering the expression of pyoverdine-related genes in P. aeruginosa, suggesting a novel link between virulence gene expression, cell-cell interaction and the multicellular community lifestyle.